Efektivitas Beberapa Jenis Pupuk Nitrogen pada Pembibitan Tanaman Kakao (Theobroma cacao L.) - Mutaqin, Zaenal; Pratiwi, Selvi; Yunita, Tika Rahma; Yama, Danie Indra; Solihin, Eso (Universitas Batanghari Jambi, 2025)
This study aims to determine the most effective type and dosage of nitrogen fertilizer in cocoa nurseries and to evaluate the level of nitrogen absorption by cocoa seedlings with various types and dosages of nitrogen fertilizer. This study was conducted at the Experimental House of the Plantation Crop Cultivation Study Program, Pontianak State Polytechnic. The method used was a non-factorial Randomized Block Design (RAK). The experiment consisted of 10 treatments, each repeated 3 (three) times, resulting in a total of 30 experimental units. Each unit consisted of two plants, resulting in a total of 60 plants. The parameters observed in this study included plant height, number of leaves, leaf area, plant fresh weight, plant dry weight, and nitrogen absorption. The type and dosage of nitrogen fertilizer significantly affected plant height, leaf area, and nitrogen absorption. The highest nitrogen absorption rate in cocoa plants was obtained with nitrate fertilizer at a dose of 2.07 g N, resulting in an absorption value of 10.51%. Urea, ZA, and Calcium Nitrate fertilizers at a dose of 1.38 g N were found to be the most effective and recommended, as the use of smaller amounts of fertilizers produced results that were not significantly different compared to the use of Urea, ZA, and Calcium Nitrate at a dose of 2.07 g N.